The Financial Settlement in the Enlargement of the European Union: Lessons for Romania? - Alan Mayhew (Romanian Journal of European Affairs, 2003)
At the end of every European Union accession negotiation, there is a fight about finance. Yet finance is by no means the most important element of the negotiations. Matters affecting the vital interests of new and old members like the free movement of labour or the representation of the new member state in the institutions of the Union are usually far more important in the longer term. But it is easier for politicians to talk to voters about money than about policy. The budgetary negotiations in this first enlargement to the countries of Central and Eastern Europe were perhaps more important in that these are relatively poor countries compared to the Union average per capita gross domestic product. They all will have to invest heavily in transport and environmental infrastructure in the coming decades in order to catch up with the standards of the EU-15 and support higher economic growth and development. Assuming responsible macro-economic policy in the new member states, EU budgetary transfers can speed up this investment process considerably, allowing these countries to catch up with the old member states in terms of per capita income more quickly. Higher transfers to the new member states means of course larger net budgetary contributions for the old member states (EU-15). This comes at a time when budget deficits are high and rising throughout the EURO-zone and when member states are making politically controversial cuts in social spending. The fiscal discipline involved in membership of the monetary union and implementation of the Broad Economic Policy Guidelines therefore means that the existing member states of the Union are not keen to see their net budgetary position with Brussels deteriorate or even their gross contributions to the budget rise. This paper investigates the background to the budget negotiations and the political economy behind them.